Comparing whole-class discussion and task-based activity. Issue 1 (4th May 2021) - Farzaneh, Thoraya; Benati, Alessandro
Abstract : This study examined the participation patterns and effectiveness of two different instructional treatments: Treatment One consisted of a task-based activity; Treatment Two used a whole-class discussion approach (Q/A paradigm). The research investigated which instructional treatment was more relevant and effective. The quantity of information learners could remember immediately after instruction, one week later, and the information that emerged through the interactional formats were measured. Each treatment was carried out for approximately one hour and then participants were asked to write a summary. After a week, students were given a piece of paper to summarise what was carried out the week before to see how much information they could remember. All the interactions were transcribed. L2 learners' response towards the task based activity showed positive results and the task-based activity treatment was considered a better pedagogical approach.